2007
DOI: 10.15288/jsad.2007.68.738
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Their Influence on Drinking Behaviors: Differences Related to Cognitive Impairment in Clients Receiving Alcoholism Treatment

Abstract: Objective-Mechanisms of behavioral change that support positive addiction treatment outcomes in individuals with co-occurring alcohol-use disorders and cognitive impairment remain largely unknown. This article combines person-and variable-centered approaches to examine the interrelated influence of cognitive impairment and social support on stability of and changes in drinking behaviors of Project MATCH (Matching Alcoholism Treatments to Client Heterogeneity) outpatients and aftercare clients (N= 1, 726) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Clients listed up to 12 individuals in their social network during the past 6 months and reported the type (e.g., family, friend) and length of relationship; frequency of interaction; members' drinking and drug-using habits; how well liked and important the client considered each; and the 4 most important people's attitudes toward the patient's substance use, abstinence, and treatment. Eight binary variables from Buckman et al (2007) were derived from the raw Important People and Activities data for the LCA. For each of the eight respective variables, a code of "1" was given if (1) at least one network member was abstinent or a light substance user, supported the client's abstinence, and interacted three or more times per week with the client; (2) at least one network member was a heavy substance user, supported the client's substance use, and interacted three or more times per week with the client; (3) all members of the network supported abstinence; (4) all members of the network encouraged drinking/drug use; (5) two or more nonusers were within the social network; (6) three or more heavy substance users were within the network; (7) daily contact was maintained with at least four network members; or (8) daily contact was maintained with at least half of the members in the social network.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Clients listed up to 12 individuals in their social network during the past 6 months and reported the type (e.g., family, friend) and length of relationship; frequency of interaction; members' drinking and drug-using habits; how well liked and important the client considered each; and the 4 most important people's attitudes toward the patient's substance use, abstinence, and treatment. Eight binary variables from Buckman et al (2007) were derived from the raw Important People and Activities data for the LCA. For each of the eight respective variables, a code of "1" was given if (1) at least one network member was abstinent or a light substance user, supported the client's abstinence, and interacted three or more times per week with the client; (2) at least one network member was a heavy substance user, supported the client's substance use, and interacted three or more times per week with the client; (3) all members of the network supported abstinence; (4) all members of the network encouraged drinking/drug use; (5) two or more nonusers were within the social network; (6) three or more heavy substance users were within the network; (7) daily contact was maintained with at least four network members; or (8) daily contact was maintained with at least half of the members in the social network.…”
Section: Methodsmentioning
confidence: 99%
“…The present study examined the hypothesis that these three social support classes would be captured in a more heterogeneous sample of clients receiving treatment for an alcohol-use disorder, drug-use disorder, or dual alcohol-and drug-use disorders. Buckman et al (2007) further found that the stability of drinking over the fi rst year after treatment, as well as the average level of cognitive impairment at treatment entry, differed across the social support classes. Clients with a high probability of social networks that supported drinking were drinking more heavily, stably, and/or problematically over the year following treatment, and they were unable to maintain a moderate or unproblematic drinking status, compared with clients with a high probability of frequent contact with an abstinence-supporting network.…”
mentioning
confidence: 92%
See 3 more Smart Citations